CHEMICAL COMPOSITION OF CHICKPEA - S. Sots; I. Kustov; I. Butsenko; I. Solonytska (Zernovì Produkti ì Kombìkorma)
Chickpea (Cicer arietinum L.), one of the oldest cultivated plants, is grown in two main varieties: desi and kabuli. The origin of chickpea is associated with the regions of the so-called "Fertile Crescent," covering modern territories of Turkey, Syria, Iraq, and Iran. Throughout various historical periods, chickpea has played an important role in ensuring food security as a source of protein essential for physical endurance. In Ukraine, chickpea is not a traditional legume crop; it is cultivated in small quantities, primarily in the southern regions. A review of the Register of Plant Varieties Suitable for Distribution in Ukraine of 2024 indicates 22 chickpea varieties approved for cultivation in the country. Both varieties of chickpea – desi and kabuli – are registered in the Ukrainian register. In 2010, Ukraine implemented DSTU 6019:2008 "Chickpea. Technical Conditions," which applies to chickpea seeds intended for food, feed, and export purposes. A preliminary analysis revealed that despite the presence of certain cereal products based on chickpea grain in Ukraine, there is no official regulation for its processing. This absence of regulation limits its widespread use as raw material for cereal enterprises. Processing is currently carried out under technical and technological instructions that often lack scientific justification, especially regarding processing regimes that affect antinutritional factors and the final product quality. An important first step in studying and scientifically substantiating the most suitable chickpea varieties and types for domestic industry is determining the chemical composition of chickpea grains, particularly for both desi and kabuli varieties. Based on this analysis, potential directions for chickpea processing in Ukraine can be identified. During the analysis of the chemical composition, it was determined that the desi variety of chickpea is characterized by smaller, dark seeds with a rough texture. It is considered richer in dietary fiber and antioxidant compounds. Desi chickpea seeds contain a significant amount of protein (on average 18-22%), making them a valuable source of plant-based protein. Carbohydrates constitute the primary component of its chemical composition, mainly in the form of easily digestible starch. Additionally, the desi variety has a high content of dietary fiber, which supports digestive health. An important feature of desi chickpea is the presence of phenolic compounds, particularly flavonoids and tannins, which provide antioxidant effects and may reduce the risk of chronic diseases. The desi variety is also rich in micronutrients, including iron, zinc, magnesium, and phosphorus, which play a crucial role in metabolic processes. On the other hand, the kabuli variety has larger, lighter seeds with a smooth surface, making it more popular for culinary use in many regions. Its chemical composition is also rich in proteins (approximately 17-21%), but its fiber content is slightly lower compared to the desi variety. The primary carbohydrate component in kabuli chickpea is starch as well, but its seed texture indicates a higher proportion of easily digestible elements. Furthermore, kabuli chickpea contains fewer phenolic compounds, contributing to its milder flavor and lighter color. The kabuli variety also contains iron, magnesium, and phosphorus in its mineral complex, though their concentrations may be slightly lower than in the desi variety. At the same time, kabuli chickpea has a higher content of monounsaturated fatty acids, making it beneficial for cardiovascular health. Fats in both chickpea varieties are present in small amounts (2-6%), but their composition is diverse, primarily consisting of unsaturated fatty acids that help reduce "bad" cholesterol levels. Chickpeas also contain vitamins from the B group (particularly B1, B6, etc.), essential for energy metabolism and nervous system health. Both varieties include small amounts of vitamin E, which enhances their antioxidant potential. Thus, the desi and kabuli varieties share a similar overall chemical composition but differ in the proportions of certain components. The desi variety stands out for its higher content of antioxidants and dietary fiber, while the kabuli variety is noted for its larger seed size, softer texture, and ease of culinary processing. Both varieties are valuable components of a healthy diet, offering a rich set of nutrients and beneficial properties in the production of cereals and other food products.